Umwege zum eigenen Kind Ethische und rechtliche Herausforderungen an die Reproduktionsmedizin 30 Jahre nach Louise Brown - Bockenheimer-Lucius, Gisela; Thorn, Petra; Wendehorst, Christiane (Universitätsverlag Göttingen, 2008)
Even 30 years after the birth of the first "artificially produced baby Louise Brown in 1978, the desire for a child remains unfulfilled for many couples. Their hopes are to modern techniques of assisted reproduction. Reproductive medicine has since made enormous progress and opens up new opportunities. With these opportunities, however, are also linked new challenges, their moral and legal implications are considerable.